Subchronic Toxicity of Green Algae (Spyrogyra sp.) Ethanolic Extract on Hematologic Parameters - Nina Salamah; Wahyu Widyaningsih; Hari Susanti; Anggita Devi; Anita Wening Sejati; Zahra Alya Putri (Intelektual Pustaka Media Utama, 2016)
Green Algae, an organism with active substance such as phytomelatonin, has potential to be developed as Indonesian traditional medicine. As the long term addition of Green Algae ethanol extract (Ekstrak etanol ganggang hijau, EEGH) influences the hematology system, in this paper, the safety test was done to ensure the safety of its use through subchronic toxicity test of EEGH on the hematology parameters of Wistar rats. The test group consisted of three groups treated with EEGH 100 mg/kg, 200 mg/kg, and 400 mg/kg, while the control group was given by 0.5% CMC-Na, with 8 rats each respectively. By using blood samples taken from orbital sinus on the 29th day, common hematologic parameters (erythrocytes, leukocytes, and hemoglobin level), the parameters of hemostasis (platelets, pT, aPTT, BT) and immune parameters (Differential Leukocytes Counts include neutrophils segment, lymphocytes, monocytes, and eosinophils) were finally observed and showed that the 28 days-addition of EEGH increase the hematological parameters of Wistar rats.